Global and Bangladesh food security outlook to 2050: challenges, systemic risks, and strategic pathway for sustainable food systems (Bangladesh Journal of Nuclear Agriculture, 2025)
Bangladesh is an agricultural country. The population of this country is increasing leading to increased food demand. Besides various factors, including urbanisation, climate change, fast changing dietary habits are making feeding about ten thousand million people by 2050 as one of the biggest challenges of this time. Vulnerabilities in the global food system are highlighted by ongoing poverty, malnutrition, and rising inequality, despite the fact that global food production has increased dramatically. There are studies on Vision 2050, its goal, but no detailed identification of the problems and opportunities associated with achieving food security in the context of Bangladesh, as well as the Global world. Within the context of Vision 2050 and in accordance with Sustainable Development Goal 2 (Zero Hunger), this paper examines the opportunities and difficulties related to attaining food security. This narrative review synthesizes evidence from peer-reviewed literature, international reports, and policy documents to examine the multidimensional nature of food security-availability, access, utilization, and stability-within the framework of Vision 2050 and Sustainable Development Goal 2. The review highlights climate change and economic shocks as major risk that disrupt agricultural productivity, supply chains, and nutritional outcomes, particularly in developing countries. Bangladesh is examined as a case study, revealing notable progress in food availability alongside persistent regional disparities, climate vulnerability, land constraints, and nutritional imbalances. In Bangladesh, strengthening smallholder farmer support, integrating indigenous knowledge with climate-smart technologies, expanding climate information services, and reinforcing social safety nets are identified as key priorities. Overall, according to this review, achieving resilient and equitable food systems by 2050 will require coordinated, evidence-based strategies that balance productivity, environmental sustainability, and social equity at both global and national levels.Bangladesh J. Nuclear Agric, 39(2): 147-162, 2025